Methylparaben concentration in commercial Brazilian local anesthetics solutions - Gustavo Henrique Rodriguez da Silva; Carla Beatriz Grespan Bottoli; Francisco Carlos Groppo; Maria Cristina Volpato; José Ranali; Juliana Cama Ramacciato; Rogério Heládio Lopes Motta (University of São Paulo, 2012)
OBJECTIVE: To detect the presence and concentration of methylparaben in cartridges of commercial Brazilian local anesthetics. MATERIAL AND METHODS: Twelve commercial brands (4 in glass and 8 in plastic cartridges) of local anesthetic solutions for use in dentistry were purchased from the Brazilian market and analyzed. Different lots of the commercial brands were obtained in different Brazilian cities (Piracicaba, Campinas and São Paulo). Separation was performed using high performance liquid chromatography (HPLC) with UV-Vis detector. The mobile phase used was acetonitrile:water (75:25 - v/v), pH 4.5, adjusted with acetic acid at a flow rate of 1.0 ml.min-1. RESULTS: When detected in the solutions, the methylparaben concentration ranged from 0.01% (m/v) to 0.16% (m/v). One glass and all plastic cartridges presented methylparaben. CONCLUSION: 1. Methylparaben concentration varied among solutions from different manufacturers, and it was not indicated in the drug package inserts; 2. Since the presence of methylparaben in dental anesthetics is not regulated by the Brazilian National Health Surveillance Agency (ANVISA) and this substance could cause allergic reactions, it is important to alert dentists about its possible presence.